Mariborska župnika, kasnejša sekovska škofa, Ulrik II. pl. Paldauf (1297-1308) in Wocho (1317-1334) - Mlinarič, Jože (Studia Historica Slovenica, 2016)
In the Middle Ages noble, highly educated priests, holding high ecclesiastical offices competed for the prestigious and rich Maribor parish. For example, the first three known priests were from the genus of Maribor lords and two of the priests even became Sechau bishops. These two were Ulrich II. pl. Paldauf (1297-1308) and Wocho (1317-1334). Ulrich was the vidame of Salzburg and a priest in Ptuj (1290), at the same time as he was the Archdeacon for the Lower margraviate (1296). Ulrich was mentioned as a priest of Maribor since the year 1295, a role he probably maintained until the year 1300. Wocho was mentioned as Ulrich's successor as a priest of Maribor in several documents belonging to our monasteries or those nearby (Viktring, Žiče monastery, St. Paul in Carinthia and Studenice) in the years 1300-1315.
Keywords: cerkvena zgodovina; Maribor; srednji vek; župnije